Effects of Older Donor Age and Cold Ischemic Time on Long-Term Outcomes of Heart Transplantation - Reich, Heidi J. (Tex Heart Inst J, 2018)
Using older donor hearts in cardiac transplantation may lead to inferior outcomes: older donors have more comorbidities that reduce graft quality, including coronary artery disease, hypertension, diabetes mellitus, and dyslipidemia. Shorter cold ischemic times might overcome the detrimental effect of older donor age. We examined the relationship between donor allograft age and cold ischemic time on the long-term outcomes of heart transplant recipients. rom 1994 through 2010, surgeons at our hospital performed 745 heart transplantations. We retrospectively classified these cases by donor ages of <50 years (younger) and ≥50 years (older), then by cold ischemic times of <120 min (short), 120 to 240 min (intermediate), and >240 min (long). Endpoints included recipient and graft survival, and freedom from cardiac allograft vasculopathy, nonfatal major adverse cardiac events, and rejection. For intermediate ischemic times, the 5-year recipient survival rate was lower when donors were older (70% vs 82.6%; P=0.02). This was also true for long ischemic times (69.8% vs 87.6%; P=0.09). For short ischemic times, we found no difference in 5-year recipient or graft survival rates (80% older vs 85.6% younger; P=0.79), in freedom from nonfatal major adverse cardiac events (83.3% vs 91.5%; P=0.46), or in freedom from cardiac allograft vasculopathy (50% vs 70.6%; P=0.66). Rejection rates were mostly similar. Long-term graft survival in heart transplantation patients with older donor allografts may improve when cold ischemic times are shorter.